2010
DOI: 10.1254/jphs.10170fp
|View full text |Cite
|
Sign up to set email alerts
|

Congo Red, an Amyloid-Inhibiting Compound, Alleviates Various Types of Cellular Dysfunction Triggered by Mutant Protein Kinase Cγ That Causes Spinocerebellar Ataxia Type 14 (SCA14) by Inhibiting Oligomerization and Aggregation

Abstract: Abstract. Several missense mutations in the protein kinase Cγ (γPKC) gene have been found to cause spinocerebellar ataxia type 14 (SCA14), an autosomal dominant neurodegenerative disease. We previously demonstrated that the mutant γPKC found in SCA14 is susceptible to aggregation that induces apoptotic cell death. Congo red is widely used as a histological dye for amyloid detection. Recent evidence has revealed that Congo red has the property to inhibit amyloid oligomers and fibril formation of misfolded prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 50 publications
2
8
0
Order By: Relevance
“…Although Congo red could be an effective treatment for dysfunctions that are triggered by mutant γPKC, it is not an ideal compound for the treatment of SCA14 because of its low permeability to the BBB, the carcinogenic activity of its metabolites, and its toxicity (33). We confirmed that a higher concentration of Congo red induced an aberrant morphology of PC dendrites (32). Because there are several derivatives of Congo red that have an improved ability to cross the BBB (33), these derivatives may be more suitable for SCA14 treatment than Congo red.…”
Section: Exploration Of Novel Therapeutics Against Dysfunctions Triggsupporting
confidence: 65%
See 1 more Smart Citation
“…Although Congo red could be an effective treatment for dysfunctions that are triggered by mutant γPKC, it is not an ideal compound for the treatment of SCA14 because of its low permeability to the BBB, the carcinogenic activity of its metabolites, and its toxicity (33). We confirmed that a higher concentration of Congo red induced an aberrant morphology of PC dendrites (32). Because there are several derivatives of Congo red that have an improved ability to cross the BBB (33), these derivatives may be more suitable for SCA14 treatment than Congo red.…”
Section: Exploration Of Novel Therapeutics Against Dysfunctions Triggsupporting
confidence: 65%
“…We also examined the effects of Congo red (32), which is widely used as an amyloid dye and has the ability to inhibit oligomerization and fibrillization with an amyloid structure (33). Similar to trehalose, Congo red inhibited aggregation and oligomerization of mutant γPKC, thereby preventing the induction of apoptosis and alleviating aberrant morphology of PCs.…”
Section: Exploration Of Novel Therapeutics Against Dysfunctions Triggmentioning
confidence: 99%
“…It is also possible that the point mutations do affect biological activity differently, but this may not be the crucial aspect for the development of the disease, which could e.g. be promoted by protein aggregation [14, 15] of other mechanisms [29]. Taken together, our findings show, that biological activity of PKCγ is affected in opposing ways for catalytic versus regulatory domain mutations but the reasons for the similar neuropathological changes in both conditions still remain elusive.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Yamamoto et al (2010) reported that stimulation of autophagy provoked by treatment with rapamycin can promote the degradation of mutant PKCγ enzymes, while normal kinases are not affected. Moreover, aggregate formation and the cytotoxicity induced by mutant γPKCs has been reported to be inhibited in SH-SY5Y cells by congo red, a dye known to inhibit amyloid oligomers and fibril formation of misfolded proteins (Seki et al, 2010). Various groups, including ours, have shown that EGCG and resveratrol can stimulate autophagy in various types of cells, including macrophages (Li et al, 2011; Kim et al, 2013; Pallauf and Rimbach, 2013), and prevent the formation of Aβ oligomers and fibrils (Bastianetto et al, 2006, 2008; Cheng et al, 2013), suggesting that polyphenols may be beneficial in the treatment of SCA14 patients.…”
Section: Discussionmentioning
confidence: 99%